The Hidden Curriculum of Youth Policy: A Dutch Example. (May 2014) - Hopman, Marit; de Winter, Micha; Koops, Willem
Youth policy is more than a mere response to the actual behavior of children, but it is equally influenced by values and beliefs of policy makers. These values are however rarely made explicit and, therefore, the authors refer to them as "the hidden curriculum" of youth policy. The study investigation explicates this hidden curriculum by empirically analyzing policy reports and interviews with policy makers. The study design is based on an existing theory on the content and structure of values. The results show that Dutch youth policy is most dominantly guided by security values. The results also show that there are differences between the social groups the policy measures target. Policy measures regarding "normal" families are becoming increasingly empowering, for example, by putting an emphasis on the competencies of parents. For families at risk, however, the focus is on control over these families by both professionals and citizens.